A study on the factor that influence organ donation awareness among students of International College of Yayasan Melaka (ICYM) / Aman Kamarudin and Muhammad Haziq Zainal - Kamarudin, Aman; Zainal, Muhammad Haziq (Faculty of Administrative Science and Policy Studies, 2012)
The scarcity of the organ available for donation and transplant remains a problematic issue in all countries including Malaysia. There have been reported that the awareness among the citizens in Malaysia is still in the lower rate compared to other developed countries. There are about 15,420 Malaysian were waiting for organ transplant and surprisingly the waiting list for organ donation remain grow longer each days. The reason of refusal of public to donate their organ is related to public attitudes, lack of knowledge, mindset, prejudices and misconception towards organ donation upon death. Even all religion has encouraged for organ donation and many campaigns have been conducted but it stills not enough to meet demand of patient for organ transplant. This situation has leads to the shortage of organ supplying due to low public awareness to pledges for organ donation. Based on these issues, this study was conducted to determine the public awareness towards organ donation in International College of Yayasan Melaka by specifically focused on the students in the institutions. A sample of 291 students was involved in this study, however, there only 147 questionnaires were received. The main objective of this study is to determine the contributing factor that lead towards public awareness on organ donation whether it influenced by public attitudes, mass media and religion. The statistic techniques used in this study are Descriptive Statistics, Regression Analysis, Spearmen Correlation and Intelligence Measurement. This study revealed that the most contributing factor that leads to public awareness towards organ donation is religion. Moreover, there only moderate relationship public attitudes, religion and mass media. The main barriers factor that has been identifying that cause public to refuse to donate their organ is due to fear and lack of knowledge. Parental consent also the constraint that cause public not to donate their organ. Therefore we can see that public have a right attitude and aware that religion, mass media have encourage them to donate their organ but it’s depend on the public itself to have courage and knowledge to realize the important of saving other people life through organ donation.